EVALUASI AKUSTIK RUANG KULIAH SEBAGAI UPAYA PENINGKATAN EFEKTIVITAS DAN PRODUKTIVITAS PROSES BELAJAR MENGAJAR - Ishak, Rahmi Amin (FORUM BANGUNAN, 2013)
Lecture room as a place of education requires a tranquility in the learning process. To improve the effectivity and productivity of lecture activities, then the purpose of this study was to determine the acoustic conditions of the environment and room on the building of the Architecture Department of Hasanuddin University, Tamalanrea, based on the potential noise levels. Evaluation of the lecture room acoustics based on the parameters: noise criteria (NP), noise insulation, direct arrivals, Reverberation Time (RT), warmth, intimacy, and diffusion. The results of the study in general shown that environmental conditions and lecture room has not fulfilled the criteria for appropriate acoustics, so it requires improvements to the room acoustic design. Keywords: lecture room, the acoustics, the learning process